A single evolutionarily divergent mutation determines the different FAD‐binding affinities of human and rat NQO1 due to site‐specific phosphorylation. Issue 1 (9th December 2021) - Pacheco‐Garcia, Juan Luis; Loginov, Dmitry; Rizzuti, Bruno; Vankova, Pavla; Neira, Jose L.; Kavan, Daniel; Mesa‐Torres, Noel; Guzzi, Rita; Man, Petr; Pey, Angel L.
Abstract : The phosphomimetic mutation S82D in the cancer‐associated, FAD‐dependent human NADP(H):quinone oxidoreductase 1 (hNQO1) causes a decrease in flavin‐adenine dinucleotide‐binding affinity and intracellular stability. We test in this work whether the evolutionarily recent neutral mutation R80H in the vicinity of S82 may alter the strong functional effects of S82 phosphorylation through electrostatic interactions. We show using biophysical and bioinformatic analyses that the reverse mutation H80R prevents the effects of S82D phosphorylation on hNQO1 by modulating the local stability. Consistently, in rat NQO1 (rNQO1) which contains R80, the effects of phosphorylation were milder, resembling the behaviour found in hNQO1 when this residue was humanized in rNQO1 (by the R80H mutation). Thus, apparently neutral and evolutionarily divergent mutations may determine the functional response of mammalian orthologues towards phosphorylation. Abstract : Phosphorylation at S82 in the human NADP(H):quinone oxidoreductase 1 (hNQO1) leads to strong functional consequences. About 20 million years ago, the mutation R80H occurred close to this site that may have made hNQO1 sensitive to the effects of S82 phosphorylation. We support this notion with comparative studies on rat NQO1, which contains R80, and hNQO1, which contains H80.